Analysis of Economic Growth in ASEAN Members - Sugiyanto, Rama; Budiarty, Ida; Yuliawan, Dedy (International Journal of Social Science, Education, Communication and Economics, 2025)
The goal of the study is to analyze the factors that impact Gross Domestic Product (GDP) in five ASEAN countries from 2016 to 2022. The independent variables in this model are Export, Education (EDU), and Industry. This study employs a quantitative approach and uses panel data regression. The estimation results indicate that exports positively and significantly to economic growth. In contrast, education has a negative and significant effect on economic growth. Industry variable has a positive but insignificant impact on economic growth. The model uses the Fixed Effects Model (FEM), and the adjusted R-squared is 0.4694. These findings suggest that increasing exports contributes to economic growth. However, education should be aligned with industry needs, and the industrial sector must adapt to updated technologies to avoid deindustrialization.